Compensation in cases of mass atrocities at the International Court of Justice and the International Criminal Court - Pérez León Acevedo, Juan Pablo (2023)
Within their different mandates, the ICJ and the ICC have decided on compensation for mass atrocities, including the same factual scenarios and related dual state/individual responsibility. However, no publication has examined these developments jointly and comparatively. Thus, this article seeks to determine how both courts are and should be developing compensation jurisprudence on mass atrocity cases. This article suggests that these two courts should construe a coherent, principle-based, and human rights-oriented international law of compensation for mass atrocities. Despite the differences in the compensation law and practice of the ICJ and the ICC, there are common elements such as the violation of an international obligation (wrongful act/international crime), damages, and the causal link between them. There are also some similarities concerning compensation goals, proof matters, and damage valua- tion. Both courts can and should conduct an adapted use of each other’s jurisprudence, considering their different mandates rather than doing so mechanically.